Parenting style and socio-emotional perspective of adolescent in Rizal High School - Ye, Yin (Manila : National University, 2016)
The earliest and most extensive learning regarding social and emotional relationships of adolescents usually starts and occurs within the family or household. Social and emotional development are strongly linked and sometimes studied or reported in tandem. Parents play an important role in emotional development, but as the child's world expands, other people in the social context also play a part in their emotional development.
Title page -- Approval sheet -- Table of contents -- List of Tables -- Acknowledgement -- Dedication -- Abstract -- Chapters I - Introduction -- Chapter II - Review of Literature -- Chapter III - Methodology -- Chapter IV - Presentation, Analysis and Interpretations of Data -- Chapter V - Summary, Conclusion and Recommendation -- References -- Appendices.
Includes bibliographical references.